ANALISIS KUALITAS PELAYANAN MENURUT KEPUASAN PELANGGAN PADA PERUSAHAAN KARGO - ., Bisri (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2022)
Customer satisfaction is implemented in 4 dimensions, namely price, service, image and overall customer satisfaction. Predicts overall customer satisfaction becomes positive and substantial when consumers perceive high service quality, perceived service delivery is the same or better than expected. This study aims to analyze the effect of service quality on customers satisfaction. The analytical method used is regression, the results of which show that service quality has a strong relationship with customer satisfaction. The results of the analysis are then followed by calculating the level of customer satisfaction for each sub-variable which results in the conclusion that of the five service dimensions assessed, the highest level of satisfaction lies in the Tangibles dimension, followed by the Assurance dimension, then the Reliability dimension, and the last is the Empathy dimension. Keywords: Service quality, customer satisfaction, tangible, assurance, reliability and empathy